Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1158/0008-5472.can-19-0024
|View full text |Cite
|
Sign up to set email alerts
|

CXCR7 Reactivates ERK Signaling to Promote Resistance to EGFR Kinase Inhibitors in NSCLC

Abstract: Although EGFR mutant-selective TKIs are clinically effective, acquired resistance can occur by reactivating ERK. We show using in vitro models of acquired EGFR TKI resistance with a mesenchymal phenotype that CXCR7, an atypical GPCR, activates the MAPK-ERK pathway via β-arrestin. Depletion of CXCR7 inhibited the MAPK pathway, significantly attenuated EGFR TKI resistance and resulted in mesenchymal to epithelial transition. CXCR7 overexpression was essential in reactivation of ERK1/2 for the generation of EGFR … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 64 publications
1
35
0
Order By: Relevance
“…Recently, it has been found that when KRAS-driven non-small cell lung cancer (NSCLC) patients were treated with epidermal growth factor receptor (EGFR) targeting therapeutic approach, significantly higher expression of CXCR7 were observed and MAPK (ERK1/2) signaling was activated, implying that EGFR and CXCR7 had a crucial interaction in NSCLC [ 37 ]. Furthermore, Becker JH et al considered that CXCR7 inhibition could prevent the emergence of acquired EGFR tyrosine kinase inhibitor (TKI) resistance in EGFR mutant NSCLC with an EMT phenotype [ 38 ]. In this study, we systematically investigate the role of CXCR7 independent of CXCR4 in lung tumor growth and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been found that when KRAS-driven non-small cell lung cancer (NSCLC) patients were treated with epidermal growth factor receptor (EGFR) targeting therapeutic approach, significantly higher expression of CXCR7 were observed and MAPK (ERK1/2) signaling was activated, implying that EGFR and CXCR7 had a crucial interaction in NSCLC [ 37 ]. Furthermore, Becker JH et al considered that CXCR7 inhibition could prevent the emergence of acquired EGFR tyrosine kinase inhibitor (TKI) resistance in EGFR mutant NSCLC with an EMT phenotype [ 38 ]. In this study, we systematically investigate the role of CXCR7 independent of CXCR4 in lung tumor growth and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…CXCR7 could also heterodimerize with Epidermal Growth Factor Receptor (EGFR) [ 46 , 47 ] to activate MAPK pathways [ 48 ]; however, the activation of the MAPK signaling by CXCR7 occurs in conditioning of EGFR inhibition with tyrosine kinase inhibitors (TKIs). CXCR7 promotes resistance to the TKI osimertinib in non-small-cell lung cancer (NSCLC) [ 49 ]. CXCR7 overexpression has recently been linked to acquired enzalutamide resistance in prostate cancer [ 50 ].…”
Section: Cxcl12/cxcr4 Axis In Tumorsmentioning
confidence: 99%
“…CXCR7 overexpression has recently been linked to acquired enzalutamide resistance in prostate cancer [ 50 ]. CXCR7 is ubiquitously overexpressed in acquired EGFR TKI resistant cell line NSCLC models with an epithelial–mesenchymal transition (EMT) phenotype [ 49 ]. While CXCR4 is known to promote EMT, the depletion of CXCR7 alone is sufficient to reverse the EMT phenotype in lung cancer models [ 49 ].…”
Section: Cxcl12/cxcr4 Axis In Tumorsmentioning
confidence: 99%
“…Recently, it has been found that when KRAS-driven non-small cell lung cancer (NSCLC) patients were treated with epidermal growth factor receptor (EGFR) targeting therapeutic approach, significantly higher expression of CXCR7 were observed and MAPK (ERK1/2) signaling was activated, implying that EGFR and CXCR7 had a crucial interaction in NSCLC [37]. Furthermore, Becker JH et al considered that CXCR7 inhibition could prevent the emergence of acquired EGFR tyrosine kinase inhibitor (TKI) resistance in EGFR mutant NSCLC with an EMT phenotype [38]. Thus it can be concluded that CXCR7 expression is strictly regulated during pathological processes especially in malignancies, which might relate to their augmented growth and migrate capacities and in line with an advantage for metastasis.…”
Section: Discussionmentioning
confidence: 99%